Focused crawling for both topical relevance and quality of medical information - Tang, Thanh; Hawking, David; Craswell, Nick; Griffiths, Kathleen (Proceedings of CIKM 2005, 2005)
Subject-speciﬁc search facilities on health sites are usually built using manual inclusion and exclusion rules. These can be expensive to maintain and often provide incomplete coverage of Web resources. On the other hand, health information obtained through whole-of-Web search may not be scientiﬁcally based and can be potentially harmful. To address problems of cost, coverage and quality, we built a focused crawler for the mental health topic of depression, which was able to selectively fetch higher quality relevant information. We found that the relevance of unfetched pages can be predicted based on link anchor context, but the quality cannot. We therefore estimated quality of the entire linking page, using a learned IR-style query of weighted single words and word pairs, and used this to predict the quality of its links. The overall crawler priority was determined by the product of link relevance and source quality. We evaluated our crawler against baseline crawls using both relevance judgments and objective site quality scores obtained using an evidence-based rating scale. Both a relevance focused crawler and the quality focused crawler retrieved twice as many relevant pages as a breadth-ﬁrst control. The quality focused crawler was quite eﬀective in reducing the amount of low quality material fetched while crawling more high quality content, relative to the relevance focused crawler. Analysis suggests that quality of content might be improved by post-ﬁltering a very big breadth-ﬁrst crawl, at the cost of substantially increased network traﬃc.
://research.microsoft.com/users/nickcr/pubs/tang_cikm05.pdf